Non-Equilibrium Thermodynamics and Outburst Hazard of a Coal Bed - Alekseev, A.D.; Feldman, E.P. (Ukrainian Journal of Physics, 2012)
We present the theoretical description of the non-equilibrium thermodynamics of a gas-bearing coal bed and the estimation of the outburst hazard of coal beds.